Exosome-Mediated Transfer of ACE2 (Angiotensin-Converting Enzyme 2) from Endothelial Progenitor Cells Promotes Survival and Function of Endothelial Cell. (20th January 2020) - Wang, Jinju; Chen, Shuzhen; Bihl, Ji
Abstract : Angiotensin-converting enzyme 2 (ACE2) is an emerging cardiovascular protective target that mediates the metabolism of angiotensin (Ang) II into Ang (1–7). Our group has demonstrated that ACE2 overexpression enhances the function of endothelial progenitor cells (EPCs). Here, we investigated whether ACE2-primed EPCs (ACE2-EPCs) can protect cerebral microvascular endothelial cells (ECs) against injury and dysfunction in an in vitro model, with focusing on their exosomal and cytokine paracrine effects on endothelial mitochondria. Human EPCs were transfected with lentivirus containing null or human ACE2 cDNA (denoted as Null-EPCs and ACE2-EPCs, respectively). Their conditioned culture media, w/wo depletion of exosomes (ACE2-EPC-CM EX-, Null-EPC-CM EX-, ACE2-EPC-CM, and Null-EPC-CM), were used for coculture experiments. EC injury and dysfunction model was induced by Ang II before coculture. Apoptosis, angiogenic ability, mitochondrion functions (ROS production, membrane potential, fragmentation), and gene expressions (ACE2, Nox2, and Nox4) of ECs were analyzed. The supernatant was collected for measuring the levels of ACE2, Ang II/Ang-(1–7), and growth factors (VEGF and IGF). Our results showed that (1) ACE2-EPC-CM had higher levels of ACE2, Ang (1–7), VEGF, and IGF than that of Null-EPC-CM. (2) Ang II-injured ECs displayed an increase of apoptotic rate and reduction in tube formation and migration abilities, which were associated with ACE2 downregulation, Ang II/Ang (1–7) imbalance, Nox2/Nox4 upregulation, ROS overproduction, an increase of mitochondrion fragmentation, and a decrease of membrane potential. (3) ACE2-EPC-CM had better protective effects than Null-EPC-CM on Ang II-injured ECs, which were associated with the improvements on ACE2 expression, Ang II/Ang (1–7) balance, and mitochondrial functions. (4) ACE2-EPC-CM EX- and Null-EPC-CM EX- showed reduced effects as compared to ACE2-EPCs-CM and Null-EPCs-CM. In conclusion, our data demonstrate that ACE2 overexpression can enhance the protective effects of EPCs on ECs injury, majorly through the exosomal effects on mitochondrial function.